Technical Efficiency of Turmeric (Curcuma Longa L.) Production in Kaduna State, Nigeria - Ayilla, V. (Journal of Agricultural Policy, 2022)
Purpose: The study analyzed the technical efficiency of turmeric production in Kaduna State, Nigeria. Methodology: Data for the study were collected with the aid of structured questionnaire from 33 turmeric farmers from Jabba, Kachia, Jama'a, and KagarkoLocal Government Areas of Kaduna State. The collected data were analyzed using descriptive statistics and stochastic frontier production function. Findings: Analysis of the results revealed that the mean technical efficiency of turmeric farmers in the study area was 28% with majority (66.7%) having technical efficiency level of â‰¤0.303. Also, analysis of the stochastic frontier production function revealed that the socio-economic characteristics of turmeric farmers in the State significantly influenced their technical efficiency. Unique contribution to theory, practice, and policy: It was recommended that campaigns aimed encouraging more youths into turmeric production as well as discouraging large household size among turmeric farmers should be promoted in the study area; and policies aimed at increasing the resource use efficiency of turmeric farmers in the State and hence their farm output should include the farmers' specific efficiency factors in their formulation.